2017
DOI: 10.1002/sia.6248
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium oxide modified with various iodine-containing compounds--Surface studies

Abstract: The activity of iodine-modified MgO in transfer hydrogenation of acrolein with alcohols can be significantly higher than that of unmodified MgO. Data from literature and our previous studies indicate that the initial source of a halide influences the surface properties and hence the activity of the obtained catalytic system. The aim of this paper is to present a systematic study on the influence of the initial source of a halide on the activity and surface properties of MgO-based catalysts. For the sake of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There are many methods of assessing the strength or concentration of basic sites found on the surface of a solid oxide. Some methods can assess only the former, e.g., the use of indicators [46], whereas other techniques can assess only the latter, e.g., titration with benzoic acid [46]. However, Temperature-Programmed Desorption of carbon dioxide can be used to determine both the strength of the sites, which is indicated by the temperature of the desorption peak, and the concentration of the basic sites, which can be obtained by integration of the area under the desorption peak [17,28,30,[47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…There are many methods of assessing the strength or concentration of basic sites found on the surface of a solid oxide. Some methods can assess only the former, e.g., the use of indicators [46], whereas other techniques can assess only the latter, e.g., titration with benzoic acid [46]. However, Temperature-Programmed Desorption of carbon dioxide can be used to determine both the strength of the sites, which is indicated by the temperature of the desorption peak, and the concentration of the basic sites, which can be obtained by integration of the area under the desorption peak [17,28,30,[47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…The high basicity of the MgO surface makes it an attractive catalyst that is used in numerous chemical processes, such as the transesterification of fats with methanol to produce fatty acid methyl esters (FAME) [12][13][14], the alkylation of phenol with methanol to 2,6-dimethylphenol [15,16], or the isomerization of a carbon-carbon double bond in the Shell Higher Olefin Process (SHOP) [17,18]. It is noteworthy that magnesium oxide is one of the most active metal oxides in the transfer hydrogenation reaction to carbonyl compounds using alcohols as hydrogen donors [19,20], although many other transfer hydrogenation catalysts continue to be widely investigated [21][22][23][24][25]. The reaction was shown to occur on supported metal and alloy catalysts, such as Au, Pt, Pd, Ru, Ag-Pd, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the supported cobalt and copper systems studied in this reaction [24] (and references therein), magnesia is a single-component system, which does not require a multi-step synthesis and is environmentally benign. Moreover, an advantage of this oxide is that it exhibits numerous basic sites along with weak Lewis acid sites on its surface [25], which are responsible for this transfer hydrogenation and can lead to high selectivity. A study of different catalytic systems conducted by Feng et al [26] showed that by-products were formed on those systems that had strong acidic sites, namely Pd/SiO 2 , Pd/Al 2 O 3 , and Pd/TiO 2 , whereas high selectivity of Pd/C and Pd/NaY was observed, which was attributed to the lack of numerous strong acid sites.…”
Section: Introductionmentioning
confidence: 99%